The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/0740817x.2015.1063793
|View full text |Cite
|
Sign up to set email alerts
|

Component procurement strategies in decentralized assembly systems under supply uncertainty

Abstract: In this article we analyze the interactions among the assembler and two component suppliers in their procurement decisions under a Vendor-Managed Inventory (VMI) contract. Under the VMI contract, the assembler rst o ers a unit price for each component and will pay component suppliers only for the amounts used to meet the actual demand. The two independent component suppliers then decide on the production quantities of their individual components before the actual demand is realized. We assume that one of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Gurnani and Gerchak [19] consider an assembler that procures components from two suppliers, and investigate the assembler's order decision and two suppliers' production decisions in the presence of random component yields. Pan and So [30] and Li et al [26] analyse the interactions among the assembler and suppliers in their procurement decisions in a random yield production system. He et al [20] study the impacts of decision sequences on a random yield supply chain with a service level constraint.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Gurnani and Gerchak [19] consider an assembler that procures components from two suppliers, and investigate the assembler's order decision and two suppliers' production decisions in the presence of random component yields. Pan and So [30] and Li et al [26] analyse the interactions among the assembler and suppliers in their procurement decisions in a random yield production system. He et al [20] study the impacts of decision sequences on a random yield supply chain with a service level constraint.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fang et al [7] study a push assembly system with multiple suppliers, simultaneous supplier contracts, and a wholesale price contract. Pan and So [30] make pricing and production decisions in an assembly system with uncertain supply under a pull contract. Other factors are also considered in the literatures related to pull and push contracts, such as the presence of an outside market [14], the impact of a hybrid push-pull contract [16], a supply chain risk-averse attitude [41], and different lead times for products [42].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(), and Pan and So () explore the inventory/production/pricing decisions for a centralized assembly system subject to random supply yields. A few papers also study contracting issues in a decentralized assembly system with random yields; see, e.g., Gurnani and Gerchak (), Güler and Bilgiç (), and Pan and So ().…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Mishra and Raghunathan [40] found that VMI intensifies the competition among manufacturers of competing brands, thus providing benefits to retailers. Pan and So [41] analyzed the interaction among the assembler and two component suppliers under a VMI contract. One supplier has uncertainty in the supply process, in which the actual number of components available for assembly is equal to a random fraction of the production quantity.…”
Section: Literature Reviewmentioning
confidence: 99%